2016
DOI: 10.1142/9789813144415_0014
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of Food Standard Determination: International Evidence from Maximum Residue Limits

Abstract: Food safety standards have proliferated as multilateral and bilateral trade agreements constrain traditional barriers to agricultural trade. Stringent food standards can be driven by rising consumer and public concern about food safety and other social objectives, or by the lobbying efforts from domestic industries in agriculture. We investigate the economic and political determinants of the maximum residue limits (MRLs) on pesticides and veterinary drugs. Using a political economy framework and econometric in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…As with those of Kandilov and Zheng (), our results indicate that the negative impact of sunk costs on the probability of export market participation is higher when the destination market is a developed country. This result confirms our expectation that nations with higher incomes adopt stricter regulation (Li et al ).…”
Section: Estimation Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As with those of Kandilov and Zheng (), our results indicate that the negative impact of sunk costs on the probability of export market participation is higher when the destination market is a developed country. This result confirms our expectation that nations with higher incomes adopt stricter regulation (Li et al ).…”
Section: Estimation Resultssupporting
confidence: 92%
“…The reason could be greater product standards over time due to consumer preferences regarding agri‐food products, especially in developed countries. Looi Kee et al () as well as Li et al () offer another potential explanation, which is that policy makers adopt more stringent regulation as tariffs are reduced by various trade agreements.…”
Section: Estimation Resultsmentioning
confidence: 99%
“…Following this framework, a number of studies are undertaken to analyze trade policy measures, both tariffs and NTMs. Among them are widely recognized works carried out by Pincus (1975), Caves (1976), Ray (1981), Lavergne (1983), Baldwin (1985Baldwin ( , 1989), Anderson and Baldwin (1987), Li, Xiong, and Beghin (2014), and Herghelegiu (2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Three decades later, the pattern of trade policy determinants changes considerably. More recently, to examine a range of the economic and political determinants of MRLs, a political economy framework together with an econometric analysis is employed in Li et al (2014). It is found that countries with higher income and larger population implement stricter MRLs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The application looks at the US shrimp market. The last manuscript in the protectionism section is unpublished and written with Bo Xiong and Yuan Li (Li, Xiong, and Beghin, 2014). It looks at the political economic determination of food standards using panel data on MRLs across countries and agricultural markets.…”
Section: Introductionmentioning
confidence: 99%